2020
DOI: 10.3390/brainsci10040234
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome in Multiple Sclerosis: Where Are We, What We Know and Do Not Know

Abstract: An increase of multiple sclerosis (MS) incidence has been reported during the last decade, and this may be connected to environmental factors. This review article aims to encapsulate the current advances targeting the study of the gut–brain axis, which mediates the communication between the central nervous system and the gut microbiome. Clinical data arising from many research studies, which have assessed the effects of administered disease-modifying treatments in MS patients to the gut microbiome, are also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 110 publications
1
58
0
1
Order By: Relevance
“…Additional therapy in combination with DMTs can be helpful. The modification of gut microbiota may serve as an additional therapeutic strategy in promoting treatment effectiveness and optimal response [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional therapy in combination with DMTs can be helpful. The modification of gut microbiota may serve as an additional therapeutic strategy in promoting treatment effectiveness and optimal response [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, EVs derived from stem/progenitor cells have been reported to inhibit proliferation and activation of immune cell and promote immune tolerance [ 25 , 26 ]. In this context, a role of placental EVs in the stem cells-microbiome connection could also be hypothesized [ 27 , 28 ]. On the other hand, almost all EV samples were negative for several surface proteins expressed by antigen-presenting cells (HLA-A/B/C molecules, CD86, and CD1c), mature or activated T cells (CD2, CD3, CD25), activated immune cells with cytotoxic properties (CD56), and B cells (CD19, CD20).…”
Section: Discussionmentioning
confidence: 99%
“…As previously emphasized, ILC3 have a central role in controlling the interaction between the gut microbiota and the host immune system. MS patients were shown to have altered gut microbiota composition, and the alterations were associated with MS pathogenesis [reviewed in (84)]. Some studies directly showed the influence of MS gut microbiota on CNS autoimmunity.…”
Section: Untangling Potency Of Gut Ilc3 Modulation For Ms Therapymentioning
confidence: 99%